PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAKANAN CEPAT SAJI MCDONALD’S DI SURAKARTA - Fx.Pudjo Wibowo (STIE Atma Bhakti, 2015)
McDonald’s in particular McDonald’s Singosaren in Surakarta day by day faces tight competition especially in fast food restaurant. Competitor especially franchise product has filled in Indonesia market. ASEAN free trade cause competition in fast food industry will increase in quality and quantity aspect. To face that competition, McDonald’s as producer which one of the best product is fried chicken should know what factors influence consumer decision making when they buy McDonald’s. We focus on marketing mix that influence consumer decision’s making. Marketing mix is practical marketing tools used by company. The purpose of this research is to test marketing mix variables that influence consumer decision making when they buy McDonald’s. The results of this research show every variables in marketing mix which are product, price, place and promotion has significant influence to consumer decision making to buy Mc Donald’s product. The biggest regression coefficient which score 0.613 0.329 is place and smallest one with regression coefficient score 0.329 is place .The tools for this test is regression analysis Which this research, McDonald’s can develop the advanced strategy to satisfy the customer to that McDonald’s get customer loyalty. With customer loyalty McDonald’s can exist in the tight competition and win the competition. Keywords: marketing mix which are product, price, place and promotion and consumer decision making